(untitled) (Bioagro, 2020)
Poor drainage has been shown as an important factor that promotes low productivity of passion fruit crop. The objective of this study was to evaluate the response of the plants after subjecting them to flooding in the soil. The trial was carried out at the UCV Agronomy School, Maracay, Venezuela, using 4-month old passion fruit plants at the flowering stage, which were grown in 9 L polyethylene bags with a peat substrate. The experimental design was a randomized complete block, with eight treatments, four replications and two plants per plot. The effect of different flood intensities on physiological performance and growth of plants was evaluated. The crop response was evaluated by determining the chlorophyll index, photosynthetic rate, transpiration, stomatal conductance, xylem water potential, fresh and dry weight of leaves, stems and roots, and root length. It was shown that passion fruit plants developed a capacity to tolerate flood conditions up to 4 days; later, there were negative effects on the variables associated with the crop physiology. Root and stem biomass were the most affected plant organs, and as the flooding time increased their weights decreased, while water content of plant tissues increased. The results indicated that passion fruit plants subjected to flooding for 5 or more days are adverse affected irreversibly.